Pentose oxidation by acetic acid bacteria led to a finding of membrane-bound purine nucleosidase - Adachi, Osao (2013)
D-Ribose and 2-deoxy-D-ribose were oxidized to 4- keto-D-ribonate and 2-deoxy-4-keto-D-ribonate respectively by oxidative fermentation, and the chemical structures of the oxidation products were confirmed to be as expected. Both pentoses are important sugar components of nucleic acids. When examined, purine nucleosidase activity predominated in the membrane fraction of acetic acid bacteria. This is perhaps the first finding of membrane-bound purine nucleosidase.